A Geography of Digestion : Biotechnology and the Kellogg Cereal Enterprise - Bauch, Nicholas (Book collections on Project MUSE., 2017)
"A Geography of Digestion explores the legacy of the Kellogg Company, one of America's most enduring and storied food enterprises. In the late nineteenth century, company founder John H. Kellogg was experimenting with state-of-the-art advances in nutritional and medical science at his Battle Creek Sanitarium. At the same time, he was involved in overhauling the form and function of the broader landscapes in which his health practice was situated. Innovations in food-manufacturing machinery, urban sewer infrastructure, and agricultural technology came together to forge an extensible geography of his patients' bodies, changing the way Americans consumed and digested food. In this novel approach to the study of the Kellogg enterprise, Nicholas Bauch asks his readers to think geographically about the process of digesting food. Beginning with the stomach, Bauch moves outward from the sanitarium through the landscapes and technologies that materialized Kellogg's particular version of digestion. Far from a set of organs confined to the epidermal bounds of the body, the digestive system existed in other places. Moving from food-processing machines, to urban sewerage, to agricultural fields, A Geography of Digestion paints a grounded portrait of one of the most basic human processes of survival--the incorporation of food into our bodies--leading us to question where exactly our bodies are located"--Provided by publisher.